Evaluation of Heterologous Biosynthetic Pathways for Methanol-Based 5-Aminovalerate Production by Thermophilic Bacillus methanolicus - Brito, Luciana Fernandes; Irla, Marta; Nærdal, Ingemar; Le, Simone Balzer; Delépine, Baudoin; Heux, Stéphanie; Brautaset, Trygve (Frontiers in Bioengineering and Biotechnology, 2021)
The use of methanol as carbon source for biotechnological processes has recently attracted great interest due to its relatively low price, high abundance, high purity, and the fact that it is a non-food raw material. In this study methanol-based production of 5-aminovalerate (5AVA) was established using recombinant Bacillus methanolicus strains. 5AVA is a building block of polyamindes and a candidate to become C5 platform chemical for the production of, among others, δ-valerolactam, 5-hydroxy-valerate, glutarate, and 1,5-pentanediol. In this study, we test five different 5AVA biosynthesis pathways, whereof two directly convert L-lysine to 5AVA and three use cadaverine as an intermediate. The conversion of L-lysine to 5AVA employs lysine 2-monooxygenase (DavB) and 5-aminovaleramidase (DavA), encoded by the well-known Pseudomonas putida cluster davBA amongst others; or lysine α-oxidase (RaiP) in presence of hydrogen peroxide. Cadaverine is converted either to γ-glutamine-cadaverine by glutamine synthetase (SpuI); or to 5-aminopentanal through activity of putrescine oxidase (Puo) or putrescine transaminase (PatA). Our efforts resulted in proof-of-concept 5AVA production from methanol at 50 °C, enabled by two pathways out of the five tested with the highest titer of 0.02 g L-1. To our knowledge, this is the first report of 5AVA production from methanol in methylotrophic bacteria, and the recombinant strains and knowledge generated should represent a valuable basis for further improved 5AVA production from methanol.